Turning microplastics into nanoplastics through digestive fragmentation by Antarctic krill - Amanda L. Dawson (Nature Portfolio, 2018)
Microplastics are emerging ocean contaminants, but their fates in the ocean environment are poorly understood. Here the authors show that Antarctic krill digest micro plastics into nano plastics, thereby generating particles of a size that can cross biological and physical barriers.